THE EFFECT OF TEACHER COMPETENCY AND JOB SATISFACTION ON PRIMARY SCHOOL TEACHER PERFORMANCE - - Sukisno; - Su’ad; - Sukirman (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2021)
ABSTRACT: The purposes of this research are: 1) to know the influence of the teacher’s competence towards to teacher’s performance, 2) to know the influence of the job satisfaction towards to teacher’s performance, 3) to know the influence of teacher's competence and job satisfaction towards to teacher’s performance. The researcher use quantitative descriptive method. This research has two independent variable, these are: variable X1 (teacher’s competence), X2 (job satisfaction), and a dependent variable Y (teacher’s performance). While the sampling technique, this research using proporsional random sampling. The results of this research are: 1) there is a positive and significant influence partially of the teacher’s preved performance. preved the value of nilai tvalue (5,023) > ttable (1,960) and pvalue (sig. = 0,000) < 0,05, 2) there is a positive and significant influence partially of the job satisfaction variable towards to teacher’s performance. This is suppated by the value of nilai tvalue (3,838) > ttable (1,960) and pvalue (sig. = 0,000) < 0,05, 3) there is positive a simultan and significant influence of the teacher’s competence variable and job’s satisfaction toward teacher’s performance. It is marked by the value of nilai Fvalue (27,515) > Ftable (3,000) and pvalue (sig. = 0,000) Keywords: Competence, Job satisfaction of teachers, Teachers ' Performance.